Low-power RFID system using analog circuit techniques based on passive sensor - Ahmad Azzreen, Dalawi; Fahmi, Samsuri (2018)
In this paper, this research introduces low-power radio frequency identification (RFID) using analog circuit techniques for passive sensors. As part of Internet of Things (IoT) transformation, RFID is widely used. In the application where power supply is limited, power consumption is always a remarkable criterion as analog circuits and RF are the common power demanding parts in the system. The proposed design for the optimized rectifier circuit, low-power analog to digital converter (ADC)/resistance to digital converter (RDC) circuit and the high efficiency regulator circuit are focused. In the design of energy harvesting rectifier circuit, the use of zero-threshold negative channel metal oxide semiconductor (NMOS)s in 18-stage rectifier circuit is improved. The high efficiency regulator circuit is added to work directly with rectifier circuit. When the energy accumulation in the charge bank that is supplied by rectifier circuit is enough, only then the regulator circuit start to produce constant voltage. To reduce the power usage of the regulator circuit, the regulator circuit avoids the use of amplifiers. In addition, a low-power ADC/RDC circuit is introduced to achieve lower power consumption by conversion scheme and novel sampling. This will minimize the total capacitance that is used by capacitance sensor (CS) array of ADC/RDC circuit by 50%. The RFID system circuit blocks on passive sensor are designed and optimized using analog circuit techniques. The demands for low-power consumption of RFID passive sensor is well examined. The validity of the proposed design is showed by both hardware measurement and simulation results.